Pan-Slavism Ideology as Shown In Sanskrit Grammars in Polish - Milewska, Iwona (Gajt Wydawnictwo 1991 s.c., 2018)
The main aim of this article is a discussion of the topic of potential influence of Pan-Slavism ideology on the grammar works of two Polish authors Walenty Skorochód Majewski (1764–1835) and Franciszek Xawery Malinowski (1807–1881). Both of them were the authors of Sanskrit grammars and both of these grammars were based on the ones written by English or German scholars. However, they are different from them in some aspects. The topic itself should be preceded by a short survey of the European tradition of the discovery of Sanskrit and its grammar. Only on this background, on the basis of comparison, it is possible to judge whether the works of Majewski and Malinowski are different from the most important grammars of the European tradition and whether they may be called ideological in their treatment of Sanskrit language and its grammar.
Keywords: Majewski, Walenty (1764-1835); Malinowski, Franciszek Ksawery (1808-1881)